Performance of coated and uncoated carbide tools while dry machining aluminium alloy - Amin Abidin, Buran (2010)
Coated and uncoated carbide tools are widely use in metal working industry. This study is to investigate the performance of coated and uncoated carbide tool while dry machining 6061 aluminium alloy in term of surface roughness. There are many factors that affect the performance of cutting tool especially when dry machining. Nowadays, there are many type of cutting tools invented by manufacture engineers to overcome the problem. As an example the coated and uncoated carbide cutting tools. This two cutting tools have their advantages and disadvantages. We try to investigate the best cutting tool whether coated or uncoated carbide cutting tool for dry machining Aluminium Alloy. Response surface methodology (RSM) was use for the analysis of the surface roughness. From this research, the result show the coated carbide tool has better surface roughness than uncoated carbide tool. The surface roughness of coated tool carbide tool can be fine when the cutting speed is 200m/min, depth of cut is 0.5mm and feed is 0.02mm/tooth. The surface roughness of uncoated tool carbide can be fine when the cutting speed is 240m/min, depth of cut is 0.5mm and feed is 0.06mm/tooth.The coated carbide tool is the most suitable in machining aluminium alloy compare to uncoated carbide tool.